Integrated ecosystems: linking food webs through reciprocal resource reliance. Issue 9 (9th August 2021) - Baruch, Ethan M.; Bateman, Heather L.; Lytle, David A.; Merritt, David M.; Sabo, John L.
Abstract: Ecosystems are defined, studied, and managed according to boundaries constructed to conceptualize patterns of interest at a certain scale and scope. The distinction between ecosystems becomes obscured when resources from multiple origins cross porous boundaries and are assimilated into food webs through repeated trophic transfers. Ecosystem compartments can define bounded localities in a heterogeneous landscape that simultaneously retain and exchange energy in the form of organic matter. Here we developed and tested a framework to quantify reciprocal reliance on cross‐boundary resource exchange and calculate the contribution of primary production from adjacent ecosystem compartments cycling through food webs to support consumers at different trophic levels. Under this framework, an integrated ecosystem can be measured and designated when the boundary between spatially distinct compartments is permeable and the bidirectional exchange of resources contributes significantly to sustaining both food webs. Using a desert river and riparian zone as a case study, we demonstrate that resources exchanged across the aquatic–riparian boundary cycle through multiple trophic levels. Furthermore, predators on both sides of the boundary were supported by externally produced resources to a similar extent, indicating this is a tightly integrated river–riparian ecosystem and that changes to either compartment will substantially impact the other. Using published data on lake ecosystems, we demonstrated that benthic and pelagic ecosystem compartments are likely not fully integrated, but differences between lakes could be used to test ecological hypotheses. Finally, we discuss how the integrated ecosystem framework could be applied in urban‐preserve and field‐forest ecosystems to address a broad range of ecological concepts. Because few systems function in complete isolation, this novel approach has application to research and management strategies globally as ecosystems continue to face novel pressures that precipitate cascading ecological repercussions well beyond a bounded system of focus.